Tikanga Māori and the rights of nature: synergies and challenges - Valmaine Toki (Isegoría)
From rising sea levels to shifting weather, patterns the effects climate change are global. Nonetheless, Indigenous Peoples are the most vulnerable to the adverse effects of climate change and yet by implementing their Indigenous worldview Indigenous Peoples are providing solutions to ameliorate the adverse effects of climate change. Unsurprisingly there is a desire to understand these Indigenous solutions. In this context, this article examines the relationship between the Māori indigenous worldview and the rights of nature, emphasizing how these concepts converge to address environmental challenges in Aotearoa, New Zealand. Māori traditions and practices provide solutions grounded in a relational ethic that acknowledges the interdependence of humans and nature. The text discusses emblematic cases, such as granting legal personhood to rivers and natural territories, illustrating how these initiatives reflect Māori values like kaitiakitanga (guardianship) and whakapapa (ancestral connection). Finally, exploring initiatives such as legal personality exemplifies differences and similarities between an Indigenous worldview and rights to nature and accounts for the advantages and challenges of integrating indigenous perspectives into contemporary legislative and political frameworks.